From blood diamonds to the Kimberley Process how NGOs cleaned up the global diamond industry - Bieri, Franziska (Routledge, 2016)
Based on extensive personal interviews with prominent campaigners, leading bureaucrats, industry officials, hundreds of KP publications, and more, this book allows for an engagement in contemporary debates about the campaign against conflict diamonds and the themes defining today's global governance arena.